2021
DOI: 10.1007/s11523-021-00824-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Infection with Immune Checkpoint Inhibitors: A Systematic Review and Meta-analysis

Abstract: Background The relative risk (RR) of infection for patients treated with immune checkpoint inhibitors (ICIs) is unknown. Objectives This study evaluated the risk of infection for patients with solid tumors undergoing ICI therapy based on a systematic review and meta-analysis. Patients and Methods The Cochrane Library, EMBASE, and Pubmed databases were searched up to 1 December 2020. Randomized trials comparing any ICI alone, with chemotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 61 publications
0
15
0
1
Order By: Relevance
“…In the case of patients with NSCLC, combining ICIs with chemotherapy inevitably increases the incidence of serious adverse events ( Petrelli et al, 2021 ). A study investigating irAEs of thoracic malignancies suggested that the incidence of elevated amylase levels in NSCLC patients caused by ICI was 0.6–3% ( Remon et al, 2018 ), which is basically consistent with this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of patients with NSCLC, combining ICIs with chemotherapy inevitably increases the incidence of serious adverse events ( Petrelli et al, 2021 ). A study investigating irAEs of thoracic malignancies suggested that the incidence of elevated amylase levels in NSCLC patients caused by ICI was 0.6–3% ( Remon et al, 2018 ), which is basically consistent with this study.…”
Section: Discussionmentioning
confidence: 99%
“…G-CSF prophylaxis is therefore indicated with the combination especially in patients with risk factors of infection during neutropenia, such as shown in Fig. 1 [107].…”
Section: Neutropenia In Therapy With Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…Many Phase 3 clinical trials have confirmed anti-PD-1 treatments in advanced NSCLC patients, either as a second-line 15–17 or first-line treatment, 18 which provided improved efficacy and survival, but not increased the infection risk. 19 Compared with second-line docetaxel chemotherapy, treatment with nivolumab or pembrolizumab provided a better ORR and OS. 20–22 The combination of anlotinib hydrochloride and Immune checkpoint inhibitors is effective and well-tolerated in patients with NSCLC.…”
Section: Introductionmentioning
confidence: 99%